A meta-analytic review of the relationship between social media use and body image disturbance - Saiphoo, Alyssa N.; Vahedi, Zahra (Computers in human behavior, 2019)
With the quickly rising popularity of social media within the past decade, researchers have started to investigate the relationship between social media use and various psychological wellbeing variables. Given social media's similarity to traditional media, and the unique types of social comparisons that may occur on these platforms, body image has been a variable of interest. However, this literature has produced mixed findings and lacks a consensus on the valence of this relationship. Thus, this meta-analysis aimed to provide a quantitative review of cross sectional research on this topic to provide clarification on the relationship between social media use and body image. An analysis of sixty-three independent samples (N = 36,552) using a random-effects model revealed an overall effect size of r = 0.169, CI [0.131, 0.206], indicating a small, positive, and significant relationship between social media use and body image disturbance. Type of social media use, body image dimension, country grouping, and age were all found to be significant moderators of this relationship. Strengths and limitations of the meta-analysis, as well as future directions for this line of research are discussed. •The valence of the relationship between social media use and body image is unclear.•A positive relationship between social media use and body image disturbance was found.•This relationship is dependent on body study-level and sample-level variables.